PARTISIPASI MASYARAKAT DALAM PENYUSUNAN RENCANA KERJA PEMERINTAH DESA (RKP DESA) DI DESA BALAI BATU SANDARAN KECAMATAN BARANGIN KOTA SAWAHLUNTO - Ali Amran,; Sartika Yuliana,; Agus Nurofik,; Fadhlan, (Jurnal Cakrawala Ilmiah, 2023)
The success of the implementation of community development is highly dependent on the role and participation of the Government and the Community. Both must be able to create synergy. Without involving the community, the government will not be able to achieve optimal development results. The problem in this research is how is community participation, what obstacles are encountered in increasing community participation and what efforts can be made to increase community participation in the preparation of the Village Government Work Plan (RKP Desa) in Balai Batu Sandaran Village, Barangin District, Sawahlunto City. This research is to find out how community participation is, what obstacles are encountered in increasing community participation and what efforts can be made to increase community participation in the Village Government Work Plan in Balai Batu Sandaran Village. The research method used is a qualitative method. Sources of data obtained are secondary data and primary data. Data collection techniques are observation, interviews and documentation, while data analysis techniques are data reduction, data presentation and data verification or drawing conclusions. Based on the results of research on community participation in the preparation of the Village Government Work Plan (RKP Desa) in Balai Batu Sandaran Village, from the results of interviews and observations it can be understood that the participation of the Balai Batu Sandaran Village community in formulating the Village Government Work Plan is still not active, because it is still low the level of community participation in the preparation and formulation of the results of the village government work plan deliberations.